2022
DOI: 10.1590/fst.71921
|View full text |Cite
|
Sign up to set email alerts
|

Effect of α-linolenic acid (ALA) on proliferation of probiotics and its adhesion to colonic epithelial cells

Abstract: The effects of α-linolenic acid (ALA) on the proliferation and adhesion of probiotics would be investigated in the present study. Effects of ALA on intestinal flora were studied by animal fecal anaerobic fermentation system in vitro, which were analyzed by high-throughput sequencing. Results showed that treatment with ALA could promote the proliferation of probiotics Lactobacillus and Bifidobacterium, and inhibit the growth of harmful bacteria Enterococcus and E. coli. ALA restored the abnormal intestinal flor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…For example, proanthocyanin B1, hesperetin, hesperidin, and (+)-catechin have excellent antioxidant capacities, 55–58 while α-linolenic acid has been shown to promote the proliferation and adhesion of intestinal probiotics. 59…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, proanthocyanin B1, hesperetin, hesperidin, and (+)-catechin have excellent antioxidant capacities, 55–58 while α-linolenic acid has been shown to promote the proliferation and adhesion of intestinal probiotics. 59…”
Section: Discussionmentioning
confidence: 99%
“…For example, proanthocyanin B1, hesperetin, hesperidin, and (+)-catechin have excellent antioxidant capacities, [55][56][57][58] while α-linolenic acid has been shown to promote the proliferation and adhesion of intestinal probiotics. 59 Excellent biological activity is an important characteristic of fermented juice. Fermentation can enhance the antioxidant capacity of food; 60,61 therefore, understanding the processes and underlying mechanisms of the digestion of food components is essential for improving health.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Research and statistical analyses have identified distinct bacterial genera in the gut microbiota and their relationship to nutrient intake. The gut microbiota can directly defend against pathogens by inducing the production of antibodies that can strengthen the defense of the host immune system after colonization of the intestinal epithelium, metabolizing indigestible compounds in food, and its role in the gut-brain axis to exert a neurological function (Liu et al, 2022). With growth and development, nutritional changes, fertility, and age, the gastrointestinal flora undergoes a physiological succession (Lozupone et al, 2012), which plays a nonnegligible role in the regulation of body health and energy metabolism.…”
Section: Relative Abundance Of Intestinal Flora In Micementioning
confidence: 99%
“…One publication stated that linolenic acid and linoleic acid at 10 to 40 µg/mL inhibited growth of Lactobacillus species (Kankaanpaa et al, 2001). On the contrary, the other publication showed that linolenic acid increased the proportion of Lactobacillus and Bi dobacterium and decreased that of Enterococcus and E. coli in vitro using rat fecal fermentation system (Liu et al, 2022). Furthermore, oleic acid but not palmitoleic acid was reported to promote growth of Lactobacillus (Endo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%